Effects of the Temporal Variability of Storm Surges on Coastal Flooding - Höffken, Jorid; Vafeidis, Athanasios T.; MacPherson, Leigh R.; Dangendorf, Sönke (Frontiers in Marine Science, 2020)
Assessments of flood exposure and risk are usually conducted for individual events with a specific peak water level and hydrograph, without considering variations in the temporal evolution (duration and intensity) of storm surges. Here we investigate the influence of temporal variability of storm surge events on flood characteristics in coastal zones, namely flood extent and inundation depth, and assess the associated flood exposure in terms of affected properties for the case of the municipality of Eckernförde, Germany. We use a nested hydrodynamic model to simulate five physically plausible, stochastically simulated storm surge events, with peak water levels corresponding to a univariate return period of 200 years and varying intensities. In a second step, the events are also combined with high-end sea-level rise projections corresponding to the RCP 8.5 scenario to analyze if the influence of temporal variability changes with rising sea-levels. Results show differences exceeding 5% in flood extent when comparing storm surges with the highest and lowest intensities. The number of properties exposed differs by approximately 20%. Differences in mean and maximum inundation depths are approximately 5%, both with and without sea-level rise. However, deviations in flood extent increase by more than 20%, depending on the sea-level rise projection, whereas differences in the number of exposed properties decrease. Our findings indicate that the temporal variability of storm surges can have considerable influence on flood extent and exposure in the study area. Taking into account that flood extent increases with rising sea-levels, we recommend that uncertainty related to the temporal variability of storm surges is represented in future flood risk assessments to ensure efficient planning and to provide a more comprehensive assessment of exposed infrastructure and assets.